ANALISIS DIRECT OPERATING COST DALAM SISTEM PENDUKUNG KEPUTUSAN PENENTUAN TIPE PESAWAT TERBANG UNTUK PEMBUKAAN RUTE BARU PENERBANGAN - Rina Widiastuti; Anton Setiawan Honggowibowo; Yuliani Indrianingsih (Institut Teknologi Dirgantara Adisutjipto, 2012)
The more commercial flights now, will be result more the number of aircraft operated and the competition to become the airline can keep operating even more difficult. Some airline companies can not compete with other companies, has gone out of business. This is one of them caused by the inaccuracy of an airline's decision in the selection of aircraft types. Type of aircraft used for flight routes should be tailored to the needs so that it can provide benefits to the company. The selection of planes is determined based on market analysis with indicators of the number of passengers, aircraft, engineering aspects of the commercial aspects or the operational costs of aircraft and competitor analysis. Aircraft direct operating costs are costs directly related to the operator of the aircraft in flight routes. Direct operating cost is very influential in the selection of aircraft types that will be used. On certain conditions the determination of the decision must be taken quickly, in which one of the conditions is the availability of relevant information. Information is the output system that can be utilized by the parties in need. Decision support system to determine the type of aircraft is a computer application that provides output in the form of aircraft operating cost information that can support managers in making decisions determining the effective fleet at the new flight routes.